Medienhessisch.: Eine Untersuchung medialer Verwendungen des „Hessischen“ - Vorberger, Lars (Linguistik Online, 2019)
The Hessian language area is characterized by the opposition of an object-linguistic heterogeneity and a perceived homogeneity. The perception and conceptualization of “Hessian” is highly connected to the medial distribution of “Hessian”. This Mediahessian hasn’t been investigated profoundly. Thus, this paper – based on an outline of the Hessian language area and the media usage of regional language – analyzes: (a) the knowledge about Mediahessian based on a survey, (b) the concept of “Hessian”, which is provided by popular scientific publications, (c) the constitutive and optional features of (TV)-Mediahessian and (d) its functions. The paper ends with a summary of the results and a definition of Mediahessian.